Nationwide Survey and Identification of Potential Stress Factor in Sensitive Skin of Chinese Women - Xiao X; Qiao L; Ye R; Zuo F (Dove Medical Press, 2020)
Xiaoqing Xiao,1,* Liyuan Qiao,2,* Rui Ye,2 Fuguo Zuo1 1Department of Dermatology, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China; 2Department of Science, Inertia Shanghai Biotechnology Co., Ltd., Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rui YeDepartment of Science, Inertia Shanghai Biotechnology Co., Ltd., No. 45 East Huaihai Road, Huangpu District, Shanghai, People’s Republic of ChinaTel +86-18681486014Email 181282251@qq.comFuguo ZuoDepartment of Dermatology, Shanghai East Hospital, Tongji University School of Medicine, No. 150, Jimo Road, Pudong District, Shanghai, People’s Republic of ChinaTel/Fax +86-021-38804518Email 873106322@qq.comPurpose: Sensitive skin is characterized by uncomfortable sensations in response to a number of factors. We performed a large-scale study to investigate the prevalence of sensitive skin at all ages and the impacts of related factors across China.Methods: A nationwide sampling of the Chinese population aged over 18 was conducted. Subjects were categorized into sensitive and non-sensitive groups, and critical differences between these two groups were investigated.Results: In total, 22,085 questionnaires were collected from Chinese women with sensitive skin. The prevalence of sensitive skin is 49.6% and is associated with age, skin type, geographic area of subjects, and other factors. Heavy life stress and the application of several cosmetic products also affect the prevalence of sensitive skin.Conclusion: Having a combination or oily skin type, living in the municipalities, being under heavy stress, and applying several cosmetic products will increase skin stress and contribute to the occurrence of sensitive skin.Keywords: Chinese women, cosmetic product usage, large-scale study, sensitive skin, skin stress